Phosphorus use efficiency and productivity as influenced by microbial inoculants in vegetable Cowpea - Meena Mary Mathew (Department of Agronomy, College of Agriculture, 1999)
An experiment was conducted at the Instructional Farm attached to the College of Agriculture, Vellayani during December 1998 - April 1999 with the objectives of finding out the role of bioinoculants viz. arbuscular mycorrhizal fungi (AMF) and phosphate solubilising microorganisms (PSM) in improving the phosphorus use efficiency and productivity in vegetable cowpea var. Sharika. The experiment was laid out in 3 x 4 + 2 factorial randomised block design with three replications. The treatments included three levels of microbial inoculants and four levels of phosphorus along with two control treatments. The study revealed that crop failed to show a significant response to the use of bioinoculants and phosphorus levels in a soil with low available nitrogen and medium phosphorus status. Biometric characters except length of vine at vegetative stage was influenced by phosphate solubilising microorganisms as well as dual application of PSM and AMF. Phosphorus application as well as interaction effect did not show a positive response on growth parameters except LAI at harvest stage where in interaction effect was significant. Bioinoculants and phosphorus application exerted a profound influence on root length and volume. Dual inoculation of AMF and PSM significantly improved root length and volume. Phosphorus application at all